ETNOBOTANI ROTAN SEBAGAI BAHAN KERAJINAN ANYAMAN MASYARAKAT SEKITAR KAWASAN TAMAN WISATA ALAM BUKIT KELAM KABUPATEN SINTANG - Siska, Lusia; Zainal, Sofyan; Sirait, Sondang Marintan (JURNAL HUTAN LESTARI, 2015)
The knowledge society is a very precious cultural wealth that needs to be explored and documented. The aim of research want to know the types of rattan what is utilized as a woven material and studying the utilization of traditional knowledge as a craft material woven rattan society About the Nature Park Hill Kelam. The sampling method used (purposive sampling) by the number of informants 84 people while the method used descriptive qualitative data analysis. From the results of the study found 10 species of rattan that is used as a material woven crafts and produce 12 kinds of webbing. Suggestions writer for rattan species that is widely used hoped the community can do a cane cultivation in order to remain sustainable existence. For this type of woven handicrafts, villagers expected Kebong can introduce handicraft products to the public outside. Extension of the weaving techniques are better supported by a rich and varied coloring is highly recommended. The need for the participation of local government initiatives and services related to the conservation of cultural specially woven handicrafts are very necessary so that the culture is maintained. Keywords : Ethnobotany, rattan, TWA Bukit Kelam, wicker.